2018
DOI: 10.1016/j.ccep.2017.11.014
|View full text |Cite
|
Sign up to set email alerts
|

When Is It Safe Not to Reimplant an Implantable Cardioverter Defibrillator at the Time of Battery Depletion?

Abstract: The implantable cardioverter defibrillator (ICD) is a life-saving therapy in various patient populations. Although data on the outcomes of initial ICD implants are abundant, data on ICD replacements, especially in patients with improved left ventricular (LV) function, are scarce. Therefore, it is not known when it is safe to not replace an ICD that has reached the end of battery life. This article reviews data on patients with primary prevention ICDs who have improvement in left ventricular ejection fraction d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 44 publications
1
5
0
Order By: Relevance
“…The results of our study support the algorithm recently proposed by Al-Khatib et al [31] to help the decision making at the time of battery depletion for both single/dual-chamber ICD and for CRT-D devices. The proposed algorithm emphasizes the need to consider LVEF, previous arrhythmias and patients engagement in order to drive the decision.…”
Section: Discussionsupporting
confidence: 87%
“…The results of our study support the algorithm recently proposed by Al-Khatib et al [31] to help the decision making at the time of battery depletion for both single/dual-chamber ICD and for CRT-D devices. The proposed algorithm emphasizes the need to consider LVEF, previous arrhythmias and patients engagement in order to drive the decision.…”
Section: Discussionsupporting
confidence: 87%
“…Left ventricular ejection fraction improvement in patients with a primary prevention ICD presents a dilemma to clinicians and patients when deciding to replace the ICD generator at the end of battery life [ 15 , 19 22 ]. Naksuk et al [ 23 ] demonstrated that patients who had an LVEF improvement to > 35% and an increase in > 10% from baseline LVEF had a similar survival benefit before and after ICD replacement when compared with patients who had no improvement in LVEF.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4] However, no guidelines exist regarding patients with primary prevention ICD implants who recover to LVEF > 35% and who have never required therapy from their ICD, at the time of generator battery depletion. 5 Since up to 45% of patients have LVEF > 35% at time of generator depletion and 65% of all ICD patients do not receive a shock before generator battery depletion, this represents a substantial patient population unaccounted for in terms of management guidelines. [5][6][7] At present, ICDs are often replaced upon battery depletion, even when the LVEF has recovered.…”
Section: Introductionmentioning
confidence: 99%
“…The utility of implantable cardioverter‐defibrillators (ICDs) for primary prevention of SCA has been demonstrated in several clinical trials, and current guidelines indicate ICD implantation for most patients with left ventricular ejection fraction (LVEF) ≤ 35% 2–4 . However, no guidelines exist regarding patients with primary prevention ICD implants who recover to LVEF > 35% and who have never required therapy from their ICD, at the time of generator battery depletion 5 . Since up to 45% of patients have LVEF > 35% at time of generator depletion and 65% of all ICD patients do not receive a shock before generator battery depletion, this represents a substantial patient population unaccounted for in terms of management guidelines 5–7 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation